Mine, All Mine - Ruth Heller's (U.S.A, 1999)
Perfect for introductory grammar and language arts lessons! What is a pronoun? How do you use it? Do you say, "These candies are for him and me"--or "he and I?" Explore language and discover how to use pronouns and their many forms from personal to reflexive to demonstrative. Praise for Mine, All Mine! ""Once again, Heller has taken a part of speech and made its function perfectly and entertainingly clear. ... From cover to cover, the stylishly drawn, brilliantly colored, double-paged illustrations grab readers and don't let go. ... Who would have thought pronouns could be such fun?"--School Library Journal" ""Bold, handsome illustrations accompanied by a jaunty, rhymed text demonstrate their importance ... with all the panache of a Madison Avenue publicity campaign. ... Language teachers, rejoice!"--The Horn Book" About the Explore! series: Dedicated to helping children learn a variety of nonfiction subjects, the Explore series uses pitch-perfect rhyming text and brilliantly illustrated images to make learning fun. Books in the series: Explore Language 1. Behind the Mask: A Book About Prepositions 2. Cache of Jewels: And Other Collective Nouns 3. Fantastic! Wow! and Unreal!: A Book About Interjections and Conjunctions 4. Kites Sail High: A Book About Verbs 5. Many Luscious Lollipops: A Book About Adjectives 6. Mine, All Mine!: A Book About Pronouns 7. Merry-Go-Round: A Book About Nouns 8. Up, Up and Away: A Book About Adverbs Explore Nature 1. Animals Born Alive and Well: A Book About Mammals and Their Young 2. Chickens Aren't the Only Ones: A Book About Animals Who Lay Eggs 3. The Reason for a Flower: A Book About Flowers, Pollen, and Seeds 4. Plants that Never Ever Bloom: A Book About Fungi, Ferns, and Other Plants Without Flowers
Keywords: Circle Time Book - Language Mechanice -- Circle Time Book - Language Mechanice